Description of two new and five known species of the genus Axonchium Cobb, 1920 (Nematoda : Dorylamida) from India with diagnostic compendia and keys to species of the genera Axonchium and Syncheilaxonchium Coomans & Nair, 1975 - Naz, Tabbasam; Ahmad, Wasim (Zootaxa, 2012)
Two new and six known species of soil-inhabiting nematodes belonging to the genus Axonchium Cobb, 1920 are describedand illustrated from India. Axonchium meghalayense n. sp. is characterized by its body length (1.6–1.9 mm), odontostylelength (9.5–10 µm), the presence of a short isthmus-like structure between the anterior and posterior parts of the pharynx,and rounded tail. The vagina in females is slightly bent posteriad, and the anterior uterine branch is a long sac. Males have41 µm long spicules, lateral guiding pieces with bifurcated distal ends, and five ventromedian supplements starting abovethe range of spicules. Body length in A. noreasum n. sp. is 1.0–1.5 mm, its odontostyle is 7–10 µm long, and the two partsof the pharynx abut each other. Females have a posteriorly directed vagina, and an anterior uterine branch 45–138 µmlong. Males have two well-spaced ventromedian supplements, spicules 30–36 µm long and conoid tail. Axonchiumamplicolle Cobb, 1920; Axonchium bulbosum Williams, 1958; Axonchium elegans Jairajpuri, 1964; Axonchium neoeletumRahman, Jairajpuri & Ahmad, 1985; Axonchium phukani Rahman, Jairajpuri & Ahmad, 1985; Axonchium parasaccatumRahman, Jairajpuri & Ahmad, 1985 are redescribed. Three recently described species, Axonchium sturhani Naz et al.,2007, A. parassaculum Naz et al., 2007 and A. singaporense Ahmad & Naz, 2010, because of their continuous lip regionwith amalgamated lips are transferred to the genus Syncheilaxonchium as S. sturhani (Naz et al., 2007) n. comb., S.parassaculum (Naz et al., 2007) n. comb. and S. singaporense (Ahmad & Naz, 2010b) n. comb. Keys and compendia to the species of the genera Axonchium and Syncheilaxonchium Coomans & Nair, 1975 are also provided.